3(x+6)=-x+8

Simple and best practice solution for 3(x+6)=-x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+6)=-x+8 equation:



3(x+6)=-x+8
We move all terms to the left:
3(x+6)-(-x+8)=0
We add all the numbers together, and all the variables
3(x+6)-(-1x+8)=0
We multiply parentheses
3x-(-1x+8)+18=0
We get rid of parentheses
3x+1x-8+18=0
We add all the numbers together, and all the variables
4x+10=0
We move all terms containing x to the left, all other terms to the right
4x=-10
x=-10/4
x=-2+1/2

See similar equations:

| 7(2x+3)-10=13×3 | | 5x+8-3x=-1 | | 3x+2+5x+26=180 | | 6-8d=-41 | | 2.5(2n-5)=7.5 | | F(7)=3x-25 | | 2/5(x-6)=3/10x+4 | | -8-2k=-k | | -13=2h | | 3.50x=42 | | 7(-2x+8)-7=-7-7x | | 4(2x-5)+2(3x-4)=16 | | ff=-8 | | 7z+2+5z+8=70 | | 30+6+30+6+x=8 | | 1/2x-x15=14 | | f/f=-8 | | 3x+2=5x+26 | | 3/x=18/26 | | •-2x–8=16 | | -9(x-1)=4(x-1) | | -7=b+5 | | 74=-7(x+4)+11 | | -6x-15=2x+1 | | 4.9t(t-4)-103=0 | | 8(7y-7)=9(5y+8) | | 3.5(2x-6)=-49.7 | | 7c=-35 | | 4.9t^2-19.6t-103=0 | | -14-7v=v+2-6v | | 20=+10(1+0.1x) | | 5d-$10.00-$4.00=$13.50 |

Equations solver categories